Genome-wide identification and characterization of the bZIP gene family and their function in starch accumulation in Chinese chestnut (Castanea mollissima Blume) - Zhang, Penglong; Liu, Jing; Jia, Nan; Wang, Meng; Lu, Yi; Wang, Dongsheng; Zhang, Jingzheng; Zhang, Haie; Wang, Xuan (Frontiers in Plant Science, 2023)
The transcription factors of basic leucine zipper (bZIP) family genes play significant roles in stress response as well as growth and development in plants. However, little is known about the bZIP gene family in Chinese chestnut (Castanea mollissima Blume). To better understand the characteristics of bZIPs in chestnut and their function in starch accumulation, a series of analyses were performed including phylogenetic, synteny, co-expression and yeast one-hybrid analyses. Totally, we identified 59 bZIP genes that were unevenly distributed in the chestnut genome and named them CmbZIP01 to CmbZIP59. These CmbZIPs were clustered into 13 clades with clade-specific motifs and structures. A synteny analysis revealed that segmental duplication was the major driving force of expansion of the CmbZIP gene family. A total of 41 CmbZIP genes had syntenic relationships with four other species. The results from the co-expression analyses indicated that seven CmbZIPs in three key modules may be important in regulating starch accumulation in chestnut seeds. Yeast one-hybrid assays showed that transcription factors CmbZIP13 and CmbZIP35 might participate in starch accumulation in the chestnut seed by binding to the promoters of CmISA2 and CmSBE1_2, respectively. Our study provided basic information on CmbZIP genes, which can be utilized in future functional analysis and breeding studies